Prevalence of Enteropathogens in Dogs Attending 3 Regional Dog Parks in Northern California. (11th November 2016) - Hascall, K.L.; Kass, P.H.; Saksen, J.; Ahlmann, A.; Scorza, A.V.; Lappin, M.R.; Marks, S.L.
Abstract : Background: The prevalence and risk factors for infection with enteropathogens in dogs frequenting dog parks have been poorly documented, and infected dogs can pose a potential zoonotic risk for owners. Hypothesis/Objectives: To determine the prevalence and risk factors of infection with enteropathogens and zoonotic Giardia strains in dogs attending dog parks in Northern California and to compare results of fecal flotation procedures performed at a commercial and university parasitology laboratory. Animals: Three‐hundred dogs attending 3 regional dog parks in Northern California. Methods: Prospective study. Fresh fecal specimens were collected from all dogs, scored for consistency, and owners completed a questionnaire. Specimens were analyzed by fecal centrifugation flotation, DFA, and PCR for detection of 11 enteropathogens. Giardia genotyping was performed for assemblage determination. Results: Enteropathogens were detected in 114/300 dogs (38%), of which 62 (54%) did not have diarrhea. Frequency of dog park attendance correlated significantly with fecal consistency ( P = .0039), but did not correlate with enteropathogen detection. Twenty‐seven dogs (9%) were infected with Giardia, and genotyping revealed nonzoonotic assemblages C and D. The frequency of Giardia detection on fecal flotation was significantly lower at the commercial laboratory versus the university laboratory ( P = .013), and PCR for Giardia was negative in 11/27 dogs (41%) that were positive on fecal flotation or DFA. Conclusions and Clinical Importance: Enteropathogens were commonly detected in dogs frequenting dog parks, and infection with Giardia correlated with fecal consistency. PCR detection of Giardia had limited diagnostic utility, and detection of Giardia cysts by microscopic technique can vary among laboratories.